2019
DOI: 10.1021/acs.inorgchem.9b00090
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Synthesis and Nucleophilic Reactivity of an Anionic Copper Superoxide Complex

Abstract: The addition of 1 equiv of KO 2 and Kryptofix222 (Krypt) in CH 3 CN to a solution of LCu(CH 3 CN) [L = N,N′-bis(2,6-diisopropylphenyl)-2,6-pyridinecarboxamide] in tetrahydrofuran at −80 °C yielded [K(Krypt)][LCuO 2 ], the enhanced stability of which enabled reexamination of its reactivity with 2-phenylpropionaldehyde (2-PPA). Mechanistic and product analysis studies revealed that [K(Krypt)][LCuO 2 ] reacts with wet 2-PPA to form [LCuOH] − , which then, deprotonates 2-PPA to yield the copper(II) enolate complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 72 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…Efforts to obtain the proposed superoxido species by addition of KO 2 (in combination with cryptand[2.2.2]) to an immobilized copper(II) complex, according to a procedure described by Bailey et al. failed [54] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to obtain the proposed superoxido species by addition of KO 2 (in combination with cryptand[2.2.2]) to an immobilized copper(II) complex, according to a procedure described by Bailey et al. failed [54] …”
Section: Resultsmentioning
confidence: 99%
“…Efforts to obtain the proposed superoxido species by addition of KO 2 (in combination with cryptand[2.2.2]) to an immobilized copper(II) complex, according to a procedure described by Bailey et al failed. [54] The monolith was treated in the same way as the functionalized silica powder and showed the same reactivity towards dioxygen at low temperatures.…”
Section: Reactivity Towards Oxygenmentioning
confidence: 99%
“…It should be noted that the reactivity of 1 (k 2 = 3.4 M -1 s -1 at -80°C) with CCA is also higher than that of a Cu(II)-superoxo complex, [Cu(βDK)(O 2 )] -(k 2 = 1.4 M -1 s -1 at -80°C), which was a highly reactive oxidant in aldehyde deformylation reported so far (Supplementary Table 8) 41 . Very recently, it has been reported that an anionic copper(II)-superoxo complex acts as a base than a nucleophile in the aldehyde deformylation of wet 2-PPA 42 . Furthermore, nucleophilic reactivity has been observed for an Fe(III) porphyrin peroxo complex in the epoxidation of electron-deficient olefins 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…We observed a low yield (28%), however, in the coupling of cyclohexylbenzene (5c) with acetophenone, perhaps due to competing side reactions that involve the cyclohexyl C-H bonds. 27 Nonetheless, addition of excess acetophenone to [Cl 2 NN]Cu-O t Bu results in second order decay of the otherwise stable copper(II) t-butoxide (Fgures S1-S2). GC/MS analysis of the resulting solution reveals the homocoupled diketone product PhC(O)CH 2 CH 2 C(O)Ph in 82% yield.…”
Section: C-h Acetylation Of Ethylbenzene With Various Ketonesmentioning
confidence: 99%